Faktor-Faktor yang Mempengaruhi Kecurangan Laporan Keuangan dalam Perspektif Fraud Triangle - Tagor Darius Sidauruk; Farhan Zulhaj Abimanyu (Penerbit Goodwood, 2022)
Purpose: This research aims to examine, analyze, and obtain evidence the factors influencing in the fraudulent financial statements in fraud triangle perspective. Method: This research’s population are Manufacturing Companies Food and Beverage Sub Sector that Listed on Indonesia Stock Exchange period 2017-2019. The sampling method used in this research is purposive sampling method and obtained a total sample of 51 companies. This research uses logistic regression analysis to examine the effects of financial stability, financial targets, external pressures, personal financial needs, nature of industry, ineffective monitoring, organizational structure, auditor turnover, audit opinion and total accruals on the fraudulent financial statements. Results: The result of this research indicated that nature of industry influences on the fraudulent financial statements. Meanwhile, financial stability, financial targets, external pressures, personal financial needs, ineffective monitoring, organizational structure, auditor turnover, audit opinion and total accruals were not influence on the fraudulent financial statements.